Crystallization and preliminary X-ray crystallographic studies of swine CD8α - Zhang, Nianzhi (International Union of Crystallography, 2011)
CD8αα homodimers or CD8αβ heterodimers form on the T-cell surface, where they are essential as co-receptors for MHC class I molecules in activation of the CTL response. To date, swine have been found to show the highest percentage of lymphocytes with surface expression of CD8α. Crystallographic analysis of swine CD8α (sCD8α) to 1.8 Å resolution revealed that the crystals belonged to space group P3(2)21, with unit-cell parameters a = 80.97, b = 80.97, c = 95.19 Å. The Matthews coefficient and the solvent content were calculated to be 3.23 Å(3) Da(−1) and 61.89%, respectively. These results may aid further structural and functional analyses of sCD8α.